Ain't my last rodeo [compact disc] - Green, Riley, 1988- (BMLG Records, 2023)
Riley Green's new album delivers more of the signature no-gimmick, undeniably country sound fans have come to know, love and obsess over. The music and lyrics, both heavily influenced by blue-collar roots and small-town life, exemplify Green's homage to his experiences, passions and love of family. The title bares its name from his poignant track, "My Last Rodeo," which Green wrote solo following one of the final conversations he had with his late Grandaddy Buford Green.